Impact of the “Mengabu (Facing Ash Storms) Disaster Preparedness” Program on Adolescents’ Knowledge About Disaster Preparedness in Kresik Tuo Village, Kayu Aro District, Kerinci Regency, Jambi - Andi Subandi; Dwi Noerjoedianto; Elsa Volinda Sary (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Natural disasters have become an integral part of people's lives in Indonesia, disrupting daily activities and causing significant impacts. Indonesia, located in the Ring of Fire, faces a high risk of volcanic eruptions, including the active Mount Kerinci which has the potential to cause disasters such as volcanic ashfall. Kresik Tuo Village, located near Mount Kerinci, faces a direct threat from this eruption. The community, especially the youth, need to improve their preparedness and knowledge to deal with potential disasters. The